Pemilihan Kepala Desa Adat Dalam Pemilihan Kepala Desa Serentak - Ibrahim, Nurmela; Pietersz, Jemmy Jefry; Bakarbessy, Andress Deny (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Due to the provisions of the law on simultaneous Village Head Elections, West Seram Regency, located in Maluku Province, is one of the districts that carry out Village Head Elections simultaneously in accordance with Regional Regulations.Purposes of the Research: 1 To analyze and find out the legal basis for the election of the Traditional Village Head in simultaneous village elections. 2. To analyze and find out the legal consequences of the election of traditional village heads which were carried out in simultaneous village head elections.Methods of the Research: The research used by the author is a normative juridical type of research, with a statutory approach and a conceptual approach. The data sources used to analyze and discuss the issues under study are secondary, primary and tertiary data sources, then legal materials obtained. Procedures for collecting legal materials and methods for analyzing legal materials.Results of the Research: Based on research obtained by Regional Regulation of West Seram Regency Number 11 of 2019 concerning Villages which stipulates that in West Seram Regency there are 92 villages This shows that there is no customary village before the simultaneous Pilkades are held according to the Village Law, it is better if the 92 villages in West Seram Regency are categorized as customary land and which are not, To answer this, the West Seram Regency Government should have ratified the legal product of the Regional Regulation on Indigenous Land.